2009
DOI: 10.1149/1.3152226
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Oxygen Transport Resistance in PEM Fuel Cells by Limiting Current Methods

Abstract: Limiting current measurements in a polymer electrolyte membrane ͑PEM͒ fuel cell are used to separate the oxygen-transport resistance into individual component parts. By varying the thicknesses of the diffusion medium ͑DM͒ and the microporous layer in different cell builds, the total transport resistance is separated into contributions from flow channels, DM, microporous layer, and all other sources. By varying the pressure, the transport resistance is separated into a pressure-dependent component ͑inter-molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
474
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 436 publications
(490 citation statements)
references
References 13 publications
11
474
0
5
Order By: Relevance
“…One method to examine a performance signature for a GDL is to analyze the resulting limiting current density on air [30,40]. To keep the analysis simple, the highest possible mass-transfer limiting current is used, thus, the concentration of oxygen at the right or liquid-inlet side of the GDL (see Figure 7) is set equal to zero.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One method to examine a performance signature for a GDL is to analyze the resulting limiting current density on air [30,40]. To keep the analysis simple, the highest possible mass-transfer limiting current is used, thus, the concentration of oxygen at the right or liquid-inlet side of the GDL (see Figure 7) is set equal to zero.…”
Section: Resultsmentioning
confidence: 99%
“…Often, a Bruggeman-type relation is used where n = 1.5; however, recent microscopic simulations and experimental studies have suggested that the value is closer to between 2 and 5 for typical GDLs [5,14,19,20,24,39,40,64]. Although, it should be noted that some of these studies change the volume fraction by compression, which alters the pore network and is different than examining a change in tortuosity and volume fraction due to pore filling.…”
Section: Updated Porous-medium Model and Modeling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Regrettably already for loadings below 0.10 mg Pt /cm² at the cathode side, the performance suffers quite drastically due to a poorly understood local resistance, which is thought to be related to an increased local mass-transport resistance (MTR), although other causes have been proposed as well. [2][3][4][5][6][7][8][9][10][11][12][13] In terms of physical interpretation, the MTR represents the local resistance of a reactant molecule towards reaching an active reaction site, which becomes more significant as the number of reaction sites decrease but the desired overall reaction rate remains the same.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Recently, a limiting-current based on a hydrogen-pump setup has been tried, which alleviates many of the issues with respect to oxygen limiting-current, but the direct applicability of the measurement towards PEFCs under operation is unknown. [20] In this study, we examine whether the MTR by hydrogen limiting-current experiments can be correlated to the overall performance loss in H 2 /air polarization curves, thereby affirming that diffusion or mass-dependent processes govern the observed performance losses with low Ptloadings.…”
Section: Introductionmentioning
confidence: 99%